New additions of bivalvia to the Peruvian marine mollusks - Paredes, Carlos (1999)
Four species of marine bivalve mollusks, Nuculana (Jupiteria) cuneata (Sowerby, 1833), Isognomon (Isognomon) janus Carpenter, 1857, Ostrea conchaphila Carpenter, 1857 and Mysella (Rochefortia) molinae Ramorino, 1968 are reported for the first time from Peruvian sea. Data are included on the geographical distribution and habitat of each species.